HIV/AIDS and tuberculosis in central Asia : country profiles - Godinho, Joana; Novotny, Thomas; Tadesse, Hiwote; Vinokur, Anatoly (Washington, DC : World Bank, 2004)
The World Bank initiated this study to address this impending crisis and assist in reducing the potentially devastating effect on human capital, economic development, and health systems reform. HIV/AIDS and Tuberculosis in Central Asia was developed to inform Bank management and other stakeholders about the main characteristics of the epidemics in the subregion; to describe differences among the countries; and to develop an understanding of the main issues related to the prevention of HIV/AIDS and the control of TB.
Includes bibliographical references: p. 83-84.
rpm 08/09/2016
Ref.
Keywords: HIV infections; HIV infections -- Asia, Central; AIDS (Disease).; AIDS (Disease) -- Asia, Central; Tuberculosis; Tuberculosis -- Asia, Central; Asia, Central